1997
DOI: 10.1177/107110079701800711
|View full text |Cite
|
Sign up to set email alerts
|

Fastest Reduction of Posttraumatic Edema: Continuous Cryotherapy or Intermittent Impulse Compression?

Abstract: Sixty patients with foot or ankle trauma were randomized and treated in three groups. In intermittent impulse compression, an air pad under the foot was inflated every 20 seconds, thus activating the venous foot pump. In continuous cryotherapy, ice water circulates between the ice box and the cold pad. The ice water was changed once per day. In standard therapy, the injured extremity was treated with cool packs, which were changed 4 times per day. Beginning at admission, every 24 hours the circumference was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 12 publications
1
46
0
2
Order By: Relevance
“…In contradiction to the findings of prior studies 18-23 , we could not find significantly different effects of the impulse compression treatment as compared with the standard treatment with ice, when the impulse compression was applied as a stand-alone treatment (with no elevation of the affected limb and no additional compression by bandage or stockinette). Stöckle et al 21 found that the impulse compression showed the fastest swelling reduction in all measured areas both before and after surgery as compared with cool packs (applied four times daily). They reported an average twenty-four-hour edema reduction of 53% preoperatively in the impulse compression group, whereas the cool pack group had a reduction of 10%.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In contradiction to the findings of prior studies 18-23 , we could not find significantly different effects of the impulse compression treatment as compared with the standard treatment with ice, when the impulse compression was applied as a stand-alone treatment (with no elevation of the affected limb and no additional compression by bandage or stockinette). Stöckle et al 21 found that the impulse compression showed the fastest swelling reduction in all measured areas both before and after surgery as compared with cool packs (applied four times daily). They reported an average twenty-four-hour edema reduction of 53% preoperatively in the impulse compression group, whereas the cool pack group had a reduction of 10%.…”
Section: Discussionmentioning
confidence: 97%
“…We suspect that positioning of the limb (with or without elevation) during impulse compression sessions and in off-session periods and the addition of a compressive force, as applied, for example, by stockinette, play an important role. There is a lack of precise description of the impulse compression application and its co-interventions in prior studies [18][19][20][21][22][23] , making comparisons of the results difficult. We believe that limb positioning and any sort of compression are potential confounders in clinical investigations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence suggests that cyclic application of external pressure with intermittent pneumatic compression provides increased arterial blood flow, decreased venous pressure, reduced venous stasis and increase the ingrowth of neurovascular tissue 16,41. Two studies reviewed examined the preliminary effectiveness of pulsatile compression on clinical outcomes and noted encouraging results 34,35. Devices that incorporate cold and intermittent compression in a controlled fashion will likely be the best option post-operatively, providing the patient with the maximum degree of comfort and the shortest time to functional recovery.…”
Section: Discussionmentioning
confidence: 99%
“…In the already mentioned study by Stöckle et al [14] also the swelling reduction at the ankle was examined by intermittent pneumatic compression with pulses compared to the use of cooling pads or continuous cooling. The compression was carried out using compression pulses of 130 mmHg, that is about 17.3 kPa, over a period of 1 s at intervals of 20 s in a pressure chamber at the sole of the foot.…”
Section: Technical Lymphatic Drainagementioning
confidence: 99%